2004
DOI: 10.1111/j.0021-8790.2004.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid–host metapopulation dynamics: the causes and consequences of phenological asynchrony

Abstract: Summary1. The strength of interaction between the specialist parasitoid Cotesia melitaearum and the host butterfly Melitaea cinxia is influenced by the coincidence of the adult stage of the parasitoid with the larval stage of the host. 2. We show that there is great variation in this developmental synchrony among local populations and among years, ranging from complete synchrony to complete asynchrony. 3. The causal mechanism is early spring temperature, which affects parasitoid development differently than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 48 publications
3
120
0
Order By: Relevance
“…By this means, the caterpillars can use cool, sunny conditions to generate adaptive phenological asynchrony with the parasitoids. In dull weather, they are not able to do this and suffer increased parasitoid attack as a result (Van Nouhuys & Lei 2004). In this situation, it seems clear that almost any change of climate would influence relative development time and, hence, the degree of butterfly-parasitoid synchrony, with consequences for the dynamics of their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…By this means, the caterpillars can use cool, sunny conditions to generate adaptive phenological asynchrony with the parasitoids. In dull weather, they are not able to do this and suffer increased parasitoid attack as a result (Van Nouhuys & Lei 2004). In this situation, it seems clear that almost any change of climate would influence relative development time and, hence, the degree of butterfly-parasitoid synchrony, with consequences for the dynamics of their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis estimates an average displacement per decade of northern and altitudinal species distribution boundaries of 6.1 km and 6.1 m northward and upward respectively (Parmesan & Yohe, 2003). In addition to the more predictable effects of abiotic factors on single species, species idiosyncratic phenological responses to changes in environmental variables are expected to trigger a cascade of changes on species interactions at all ecological levels with unpredictable consequences (Davis et al, 1998;Chapin et al, 2000;Van Nouhuys & Lei, 2004). In the present work, a comprehensive study describing CRS parasitoid assemblages in the main Spanish citrus growing areas has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies documenting this process are rare. Van Nouhuys and Lei (2004) showed that warmer, early spring-temperatures favoured the parasitoid wasp Cotesia melitaearum disproportionally, bringing it into closer synchrony with its host the butterfly Melitaea cinxia. Although the authors found no direct effect of the phenological matching on local host population size, the synchrony is likely to be important for overall host meta-population dynamics via variation in the rate of colonisation by the parasitoid.…”
Section: Matches and Mismatches Across Trophic Levelsmentioning
confidence: 99%